A decade of replication study in education? A mapping review (2011–2020). Issue 1 (17th February 2022) - Perry, Thomas; Morris, Rebecca; Lea, Rosanna
ABSTRACT: Replication studies in education are relatively rare. Of the few which are conducted, many are conceptual rather than direct replications. With so few replication studies, and many of those that are attempted producing null results, the scientific status of the evidence base for educational policy and practice is in question. Replicating Makel and Plucker's review of the education replication literature, conducted in 2014, this paper presents a mapping review looking at rates of replication in education research from 2011 to 2020. We provide an overview of the number of replication studies by replication type, year, outcome, authorship, and journal. Our results are consistent with those of Makel and Plucker, revealing very low but gradually increasing rates of replication study in education. We discuss the role of replication in producing a robust and trustworthy evidence base for policy and practice, and some of the challenges in operationalising definitions of replication we encountered.